2018
DOI: 10.1186/s12887-018-1270-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic pyloric stenosis following persistent pulmonary hypertension of the newborn: a case report and literature review

Abstract: BackgroundAlthough persistent pulmonary hypertension of the newborn (PPHN) and infantile hypertrophic pyloric stenosis (HPS) are both well-known diseases that occur in early infancy, PPHN complicated by HPS is rare. As nitric oxide (NO) is an important mediator of biological functions, on both the vascular endothelium and smooth muscle cells, the decreased production of NO might play a role in the pathogenesis of both PPHN and HPS. We present the case of a neonate who developed HPS following PPHN, including a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…This study also suggested the importance of exclusive breastfeeding in decreasing the risk of HPS (5). Due breast milk may have lower osmolality, which could provide better gastric emptying (6). The breast milk field contains macronutrients that affected the growth of a child (7).…”
Section: Introductionmentioning
confidence: 74%
“…This study also suggested the importance of exclusive breastfeeding in decreasing the risk of HPS (5). Due breast milk may have lower osmolality, which could provide better gastric emptying (6). The breast milk field contains macronutrients that affected the growth of a child (7).…”
Section: Introductionmentioning
confidence: 74%
“…This work is carried out by the placenta, which is responsible for guaranteeing the essential oxygenation of the blood, which will be directed to the fetal heart and brain to meet the high metabolic demands of the developing fetus. In fetal circulation, all blood that returns to the fetal cardiac system flows preferentially from the right atrium, through the foramen ovale to the left atrium, and is expelled through the left ventricle to be made available for the coronary and cerebral circulation (Verklan, 2006;Storme, et al, 2013;Iijima et al, 2018).…”
Section: Physiology Of Fetal Pulmonary Vascular Regulationmentioning
confidence: 99%
“…Pulmonary hypertension in the newborn may be primary (idiopathic) or secondary to lung tissue disease (such as surfactant deficiency, meconium aspiration syndrome or alveolar-capillary dysplasia), polycythemia, hypoglycemia, sepsis or maternal ingestion of prostaglandin inhibitors (Storme et al, 2013;Iijima et al, 2018).…”
Section: Pathogenesis Of Neonatal Persistent Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 , 5 , 9 , 11 , 13 15 , 19 , 22 , 24 , 39 , 44 , 45 , 47 , 48 , 52 ]…”
Section: The Clinical Algorythmunclassified